Anamnestic immune response and safety of an inactivated quadrivalent influenza vaccine in primed versus vaccine-naïve children - Claeys, C; Chandrasekaran, V; García-Sicilia, J; Prymula, R; Díez-Domingo, J; Brzostek, J; Marès-Bermúdez, J; Martinón-Torres, F; Pollard, AJ; Růžková, R; Martinez, AC; Ulied, A; et al. (Wolters Kluwer, 2018)
Background: It has not yet been demonstrated whether two doses of inactivated quadrivalent influenza vaccine (IIV4) prime a booster response in infants. We evaluated the anamnestic immune response to an IIV4 in children aged 17−48 months. Methods: Children were randomized to two doses of IIV4 or control in the primary phase III study (NCT01439360). One year later, in an open-label revaccination extension study (NCT01702454), a subset of children who received IIV4 in the primary study (primed group) received one IIV4 dose and children who received control in the primary study (unprimed) received two IIV4 doses 28 days apart. The primary objective was to evaluate hemagglutination inhibition (HI) antibody titers 7 days after first IIV4 vaccination in the per-protocol cohort (N=224 primed; N=209 unprimed). Neutralizing and anti-neuraminidase antibodies were also measured. Safety was analyzed in the total vaccinated cohort (N=241 primed; N=229 unprimed). Results: An anamnestic response was observed in primed children relative to unprimed controls, measured by age-adjusted geometric mean HI titer ratios against strains homologous (A/H1N1: 9.0; B/Victoria: 3.9) and heterologous (A/H3N2: 2.7; B/Yamagata: 6.7) to those in the primary vaccination series. The anamnestic response in primed children included increases in neutralizing antibodies (mean geometric increase: 5.0–10.6) and anti-neuraminidase antibodies (4.9–8.8). No serious adverse events related to vaccination were reported. Conclusion: In this study, 2-dose priming with IIV4 induced immune memory that was recalled with 1-dose IIV4 the following year to boost HI, anti-neuraminidase, and neutralizing antibodies, even though the IIV4 strain composition partially changed.